Analysis of the organic rice market structure in Lampung Province - Muhammad Irfan Affandi; Aan Andika; Dyah Aring Hepiana Lestari (Agriekonomika, 2024)
This study aims to determine the comparative advantage and competitive advantage of organic rice in Lampung Province. The research locations were in Punggur District, Central Lampung District, Pardasuka District and Pringsewu District, Pringsewu District. This research was conducted using survey methods and interviews with farmers using a prepared questionnaire. Respondents in this study amounted to 35 farmers who were selected deliberately using purposive sampling by the research objectives. The types of data used are primary data and secondary data. To answer the analysis objective, the Price Transmission Elasticity and the Herfindahl Hirschman Index (IHH) Policy Analysis Matrix (PAM) is used. The results showed that the market structure for the organic rice business in Lampung Province was oligopsony, as evidenced by the transmission elasticity value of 0.01151. the concentration ratio and market share results were 0.89 and 99.06%, which means that the value of the ratio concentration criteria was 70%, so that the organic rice market concentration in Lampung Province can be said to be high concentration oligopsony.